Simple Version of the Linear Business Cycle Model. - Kamill, Anton Abdulbasah; Baharum, Adam (Universiti Sains Malaysia, 2009)
The paper developed a linear business cycle model. To analyze the impact of small changes in productivity, the model is linearized around the steady state which allows us to find optimal level of consumption and investment under assumption of perfect foresight i.e, knowledge of all future values of the total factor productivity.